The efficacy of rituximab in the treatment of inhibitor-associated hemostatic disorders - Franchini, Massimo; Veneri, Dino; Lippi, Giuseppe; Stenner, Rachel (Thrombosis and Haemostasis, 2006)
Rituximab is a chimeric anti-CD20 monoclonal antibody active against normal and malignant B cells which has proven to be effective in the therapy of CD-20 positive lymphomas. Its B-cell cytotoxic action has also been exploited in many non-malignant autoimmune disorders in which it has been used with the aim of interfering with the production of pathologic antibodies. The present knowledge regarding the use of rituximab in antibodyassociated disorders of hemostasis (i.e. idiopathic thrombocytopenic purpura, thrombotic thrombocytopenic purpura, acquired hemophilia A, congenital hemophilia with inhibitors, acquired inhibitors against coagulation factors) is presented briefly in this review. The results suggest that rituximab can be useful in the treatment of disorders of hemostasis associated with inhibitor formation. Although collectively the number of patients treated is now quite substantial, most of the data are drawn from isolated case reports or descriptions of small, uncontrolled series. Large, prospective, randomized trials are, therefore, needed to confirm the positive, preliminary results.
Keywords: Rituximab; inhibitor; coagulation disorders